Workshop Peran Guru dalam Menstimulasi Perkembangan Emosi Anak Usia Dini di PKG PAUD Bayan Kabupaten Lombok Utara - Pamuji Rahayu, Eka; Prisma Mahendra, Juandra; Musafir, Musafir; Laela, Laela (Universitas Mataram, 2022)
This article discusses the important role of teachers in stimulating the emotional development of early childhood through workshops held at PKG PAUD Bayan, North Lombok Regency. By using a data-based and statistical approach, this service aims to provide insight into how appropriate teaching methods can improve children's emotional abilities. The results of the workshop showed a significant increase in teachers' understanding of the importance of children's emotional development, as well as the application of the techniques learned in the teaching and learning process